PENGARUH PEMBERIAN EKSTRAK BUAH KERSEN (Muntingia calabura L.) DOSIS BERTINGKAT TERHADAP GAMBARAN HISTOPATOLOGI GINJAL MENCIT BALB/C YANG HIPERURISEMIA - Ida Kholifaturrokhmah; Ratna Damma Purnawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Cherry fruit has flavonoid function as an antioxidant. Cherry is traditionally used to treat gout. Increased production of uric acid in the metabolism or decreased excretion (expenditure) of uric acid in the kidney can affect images of kidney histopathology.Aim : Proving there are differences in kidney histopathology picture Balb / c mice were hyperuricemia among the group given cherry fruit extract (Muntingia calabura L.) with multilevel dose control group and uric acid levels Balb/c mice.Methods : This was a true-experimental research study using the pre test and post test control group design. The sample of 30 8Balb/c mice were divided into 6 groups randomly. The K1 group which was given only standard food and beverage, K2 group which were high purin diet and standard food, K3 group which were given cherry extract, and treated groups (P1,P2,P3) which were given standard food and cherry extact in graded dosage: 14 mg/20grBW, 28 mg/20grBW, and 56 mg/20grBW. The uric acid serum level of mices were measured, then the mices were terminated for observe the microscopic changes in kidneys.Results : One Way ANOVA test for proximal tubular damage showed the insignificant difference (p>0.05) in every groups. At the level of uric acid, Wilcoxon test showed significant differences (p<0.05) in every groups.Conclusion : There were not significant difference between chery extract with graded dosage to histopatological images of hyperurisemia Balb/c mice’s kidney. But the cherry fruit significant difference of hyperuricemia Balb/c mice.